Covid-19 Pandemic as Force Majeure to Credit Agreements - Reni Anggriani; Rafid Adyatma (Universitas Muhammadiyah Yogyakarta, 2023)
Agreements are closely related to human life, including improving the economy. An agreement is an agreement of the parties, including in running the economy, including credit agreements, carried out by customers with banks. The agreed agreement must be executed by the parties. However, sometimes, not all of the contents of the agreement can be implemented, including because of Force Majeure. The study uses normative and empirical legal research to determine whether the COVID-19 pandemic can be categorized as Force Majeure in Credit Agreements. The COVID-19 pandemic can be categorized as Force Majeure in a case study at PT. Bank Rakyat Indonesia (Persero) Tbk. Gombong Branch Office). Since the COVID-19 pandemic can be categorized as a Force Majeure, the credit agreement that has been agreed at the beginning can be restructured. Accordingly, no one has investigated this issue.